Infrared Spectrum Analysis of Goji Berry during Electrohydrodynamic Drying - Jiabao Ni; Changjiang Ding; Yaming Zhang; Zhiyuan Cao; Zhiqing Song; Xiuzhen Hu; Tingjie Hao (Journal of Spectroscopy)
This paper aims to study the effects of different needle spacings on goji berry structure during electrohydrodynamic (EHD) drying. The drying characteristics and the product quality parameters of goji berry during the drying process were measured. The infrared spectrum of the dried product was analyzed in detail. The results showed that the average drying rate of goji berry under different needle spacing conditions was significantly higher than that of the control group, and the average drying rate decreased with the increase of needle spacing. The change of needle spacing has great influence on goji berry polysaccharide content and flavonoid content. Fourier transform infrared spectroscopy showed that the infrared spectra of goji berry in each treatment group were generally similar. The first-order infrared spectra of different treatment groups were mainly different in the range of 1740 cm−1 and 2800 cm−1–2950 cm−1. The shape and intensity of the absorption peaks of the second derivative infrared spectrum of goji berry in different needle spacing treatment groups were different. When the needle spacing is 2 cm and 4 cm, there is a highly variant peak ratio and a low common peak ratio, which proves that the best drying effect is at 2 cm and 4 cm. It provides experimental and theoretical basis for the study of the application and drying mechanism of infrared spectroscopy in the field of electrohydrodynamic drying.